Rupture Rates Between 2-Strand and 4-Strand Flexor Tendon Repairs: Is Less More?. Issue 1 (January 2020) - Shaharan, Shazrinizam; Bage, Timothy; Ibrahim, Nada; Diamantopoulos, Antonios; Doswell, Kirsty; Dheansa, Baljit
Abstract : Abstract: The purpose of this study was to explore the difference in clinical outcome of 2-strand and 4-strand flexor tendon repairs in a single unit in adult population. A total of 109 complete divisions of a single flexor tendon were analyzed from 2016 to 2018 retrospectively. Thirty flexor tendons were repaired with 2-strand and 79 tendons were repaired with 4-strand technique. There was no significant difference in the complication rate including rupture, infection, and adhesions. These results support that 4-strand is not superior than 2-strand and that lower volume type of repair would be preferable.